Complications and Anatomical Considerations in Botulinum Neurotoxin Type A Injections for Upper Face Rejuvenation: A Systematic Review - Kąpa, Maria; Szepietowski, Bartosz; Szustak, Jan; Wijata, Michał; Wijata, Anna Maria; Przybyłek-Stępień, Zuzanna Adriana; Bartosiński, Ryszard; Kaźmierczak, Jakub Marek; Rycerz, Ewelina; Mączyńska, Wiktoria; Dutkiewicz, Justyna; Pasek, Piotr (Quality in Sport, 2025)
Botulinum neurotoxin type A (BoNT-A) is widely utilized in aesthetic medicine for the treatment of dynamic rhytides in the upper face. Despite its efficacy, the intricate anatomy of the upper face poses significant challenges, with potential complications ranging from transient injection-site reactions to more severe outcomes such as eyelid ptosis and facial asymmetry. This systematic review aims to provide a comprehensive analysis of the complications associated with BoNT-A injections in the upper face, focusing on the interplay between anatomical variations, injection techniques, and patient-specific factors. By synthesizing current clinical evidence, this review highlights the importance of precise anatomical knowledge, standardized injection protocols, and injector expertise in minimizing adverse effects. Furthermore, it offers evidence-based recommendations to enhance the safety and efficacy of BoNT-A treatments, ensuring optimal aesthetic outcomes while mitigating risks.